Seneca : the life of a stoic - Veyne, Paul, 1930 (Routledge, 2003)
"The great stoic philosopher, playwright, and Roman statesman of the first century, Lucius Annaeus Seneca, exercised enormous influence for nearly fifteen years as tutor and political advisor to the Emperor Nero until forced to commit suicide by his former pupil. In the hands of Annales School historian Paul Veyne, the dramatic story of his life - one of power, politics, and intrigue - becomes a mirror of the time in which he lived."